The Constitutional Law Research Trends and Plagiarism Problem in State Islamic University - Ija Suntana (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2019)
The objective of this research was to find out research trend in constitutional law area as well to map research procedures in the said area and its projection in the future. Bibliometric analysis was applied, using 80 theses as sample from constitutional law bachelor degree student theses data base, with time range from 2013 to 2017. The research result shows that the Constitutional Law students gave extra preference to legislation studies rather that other subject. In methodological matters, the trend shows that most of research used descriptive methodology (45%) and only few utilized comparative methods (6%). At least 41 concepts were chosen by the students, with top four concepts are the enactment of regulations, the implementing regulations of Acts, the local government regulations, and the enactment of an article. The less chosen concepts are international law/regulations and state treasury management. From research originality aspect, by using Turnitin application, there are 28 theses that have similarity indication with previous researches (with various typologies) and 52 theses are acceptable.